Aransemen Musik Baru Kesenian Ronteg Singo Ulung pada Sanggar Gema Buana, Desa Prajekan Kidul, Kabupaten Bondowoso, Jawa Timur - Zulkarnain Mistortoify; Aris Setiawan; Mutiara Dewi Fatimah (Institut Seni Indonesia Surakarta, 2022)
This research is based on community service done, aiming to create a new musical arrangement for the Ronteg Singo Ulung art in the Gema Buana Art Community, Bondowoso Regency, East Java. The concern is on musical part which has been seen as monotonous, only present to accompany the movements of Singo Ulung dances. This research employs a participatory approach, actively involved in finding new musical pattern formulations that are considered ideal for the development of Singo Ulung art in the future. In addition, experimental work on the creation of new music is carried out while still basing it on the dynamics of the culture in which the arts live that is the Madurese community. As a result, the laboratory work process in this study resulted in more dynamic musical findings, by incorporating new musical elements so that the perception of musical monotony could be eliminated. The new music produced is continuously communicated, especially to dance choreographer, so that it can become an integral and inseparable part. Thus, the creative work of new music creation also leads the emergence of a similar step in terms of choreography.